Identification and evaluation of English accents by listeners with related native languages - Kralova, Zdena; Nemcokova, Katarina; Hrbackova, Karla; Kral, Samuel (Glottodidactica, 2024)
This study explores the identification and evaluation of English accents by non-native English speakers, specifically Czech and Slovak undergraduate students majoring in English as a Foreign Language (EFL). The research aims to determine how these students perceive and rate ten English accents, including native and non-native varieties. Using questionnaires, the study examines the correlation between the ability to identify the speakers’ native language and the evaluation of their English pronunciation quality. The findings reveal that Czech and Slovak students generally share similar evaluations of English accents, with significant differences primarily in identifying and evaluating accents related to their native languages. This research contributes to understanding how related linguistic backgrounds influence the perception and judgment of English accents, providing insights for language teaching and accent training in EFL contexts.